iTRAQ-based Proteomics Analysis of ADTM for Preventing the Development of Nitroglycerin-induced Tolerance - Hu, Huihui; Wu, Jia; Guo, Baojian; Wang, Yuqiang; Shan, Luchen (Current Pharmaceutical Analysis, 2022)
Background: Long-term nitroglycerin (NTG) therapy causes tolerance, which limits its clinical application. Previous studies have reported a novel Danshensu/tetramethylpyrazine derivative ADTM, which displays strong cardioprotective effects. However, the effect of ADTM is not known in the NTGinduced tolerance model. In this study, we aimed to evaluate the potential improvement and underlying mechanism of ADTM for preventing the development of NTG-induced tolerance in in vivo and in vitro experiments. Methods: Firstly, the effect of ADTM was determined on NTG-induced tolerance using isolated thoracic aortic rings obtained from rats (50 μM for 45 min). After intragastric administration of ADTM (30 mg/kg, twice a day) for 7 days, NTG solution (10 mg/kg) was subcutaneously injected into male Sprague-Dawley (SD) rats once a day for 7 consecutive days. The systolic arterial pressure (SAP), diastolic arterial pressure (DAP), and mean arterial pressure (MAP) were recorded using the PowerLab system. The iTRAQ-based proteomics analysis was used to clarify the underlying mechanism of ADTM in NTG-induced tolerance. Results: ADTM markedly enhanced relaxation sensitivity and vasodilator responses to NTG tolerance in the isolated rat thoracic aorta, and this effect was independent of the vascular endothelium. ADTM prevented the development of NTG-induced tolerance in rats by improving hemodynamic parameters, such as SAP, DAP, and MAP. The iTRAQ-based proteomic analysis suggests that ADTM prevention of NTGinduced tolerance may be related to the regulation of ribosomal metabolism and tight junctions. Conclusion: These results indicate that ADTM has therapeutic potential for NTG-induced tolerance, and is worthy of further studies.
Keywords: nitroglycerin